2002
DOI: 10.4319/lo.2002.47.5.1405
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale mapping of land‐derived nitrogen in coral reefs by δ15N in macroalgae

Abstract: We measured the C/N ratio and ␦ 15 N values of two brown macroalgae-Padina spp. and Dictyota sp., which are distributed over all the subtropical fringing reefs of the Ryukyu Islands, Japan-to evaluate the feasibility of these algae as indicators of the terrestrial nitrogen load to the reef. The correlations between the distance from the shoreline and algal C/N ratio and surrounding NO concentrations were not clear, although their average values among the Ϫ 3 reefs seemed to indicate differences in nitrogen loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
96
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(109 citation statements)
references
References 49 publications
9
96
1
1
Order By: Relevance
“…The low d 15 N values of the macroalgae, the low nutrient concentrations of lagoon waters, the lack of correlation between d 15 N values and distance from shore, and the low concentrations of nutrients in well-water samples indicate that the major sources of nutrients to the three Ofu-Olosega lagoons at the time of this study were most likely oceanic/atmospheric, and not animal/anthropogenic in origin. In contrast to this study, Umezawa et al (2002) found an inverse linear or curvilinear decrease in d 15 N values of macroalgae with distance from shore in the Ryuku Islands, Japan. This pattern was attributed to multiple sources of nitrogen, including terrestrial and human.…”
contrasting
confidence: 99%
“…The low d 15 N values of the macroalgae, the low nutrient concentrations of lagoon waters, the lack of correlation between d 15 N values and distance from shore, and the low concentrations of nutrients in well-water samples indicate that the major sources of nutrients to the three Ofu-Olosega lagoons at the time of this study were most likely oceanic/atmospheric, and not animal/anthropogenic in origin. In contrast to this study, Umezawa et al (2002) found an inverse linear or curvilinear decrease in d 15 N values of macroalgae with distance from shore in the Ryuku Islands, Japan. This pattern was attributed to multiple sources of nitrogen, including terrestrial and human.…”
contrasting
confidence: 99%
“…In these conditions, seagrasses should be poorer indicators of water column process than, for example, macroalgae which rely only on their surrounding water for their nutrient requirements (e.g. Gartner et al, 2002;Umezawa et al, 2002). On the other hand, the δ 15 N of species or populations which uptake a significant part of their inorganic N from sediment pore water, should be an informative indicator of environmental conditions in the sediment.…”
Section: Environmental Tracersmentioning
confidence: 99%
“…For example, foliose and filamentous macroalgae such as Ulva intestinalis could more efficiently reflect the δ 15 N-DIN variations because their faster uptake and growth rates (Teichberg et al, 2008;Dailer et al, 2010;Ochoa-Izaguirre and Soto-Jiménez, 2015). Environmental factors such as seawater nutrient levels, temperature and light may also result in the difference of macroalgal δ 15 N values (Umezawa et al, 2002;Derse et al, 2007;Viana and Bode, 2015). Although the effect of environmental nitrogen status and concentration on macroalagal fractionation remains controversial (Cohen and Fong, 2004;Dailer et al, 2010;Kaldy, 2011), significant fractionation was showed with high nitrogen concentration in the water column and high nitrogen content in macroalgae (Thornber et al, 2008;Kaldy, 2011;Viana and Bode, 2015).…”
Section: Introductionmentioning
confidence: 99%